Basic considerations in the dermatokinetics of topical formulations (Brazilian Journal of Pharmaceutical Sciences, 2013)
Assessing the bioavailability of drug molecules at the site of action provides better insight into the efficiency of a dosage form. However, determining drug concentration in the skin layers following topical application of dermatological formulations is a great challenge. The protocols followed in oral formulations could not be applied for topical dosage forms. The regulatory agencies are considering several possible approaches such as tape stripping, microdialysis etc. On the other hand, the skin bioavailability assessment of xenobiotics is equally important for topical formulations in order to evaluate the toxicity. It is always possible that drug molecules applied on the skin surface may transport thorough the skin and reaches systemic circulation. Thus the real time measurement of molecules in the skin layer has become obligatory. In the last two decades, quite a few investigations have been carried out to assess the skin bioavailability and toxicity of topical/dermatological products. This review provides current understanding on the basics of dermatokinetics, drug depot formation, skin metabolism and clearance of drug molecules from the skin layers following application of topical formulations.